Computation provides chemical insight into the diverse hydride NMR chemical shifts of [Ru(NHC)4(L)H]0/+ species (NHC = N-heterocyclic carbene; L = vacant, H2, N2, CO, MeCN, O2, P4, SO2, H−, F− and Cl−) and their [Ru(R2PCH2CH2PR2)2(L)H]+ congeners. Issue 9 (13th February 2017) - Häller, L. Jonas L.; Mas-Marzá, Elena; Cybulski, Mateusz K.; Sanguramath, Rajashekharayya A.; Macgregor, Stuart A.; Mahon, Mary F.; Raynaud, Christophe; Russell, Christopher A.; Whittlesey, Michael K.
Abstract : Relativistic DFT calculations rationalise hydride NMR chemical shifts in a range of Ru complexes. Abstract : Relativistic density functional theory calculations, both with and without the effects of spin–orbit coupling, have been employed to model hydride NMR chemical shifts for a series of [Ru(NHC)4 (L)H] 0/+ species (NHC = N-heterocyclic carbene; L = vacant, H2, N2, CO, MeCN, O2, P4, SO2, H −, F − and Cl − ), as well as selected phosphine analogues [Ru(R2 PCH2 CH2 PR2 )2 (L)H] + (R = i Pr, Cy; L = vacant, O2 ). Inclusion of spin–orbit coupling provides good agreement with the experimental data. For the NHC systems large variations in hydride chemical shift are shown to arise from the paramagnetic term, with high net shielding (L = vacant, Cl −, F − ) being reinforced by the contribution from spin–orbit coupling. Natural chemical shift analysis highlights the major orbital contributions to the paramagnetic term and rationalizes trends via changes in the energies of the occupied Ru dπ orbitals and the unoccupied σ * Ru–H orbital. In [Ru(NHC)4 (η 2 -O2 )H] + a δ-interaction with the O2 ligand results in a low-lying LUMO of dπ character. As a result this orbital can no longer contribute to the paramagnetic shielding, but instead provides additional deshielding via overlap with the remaining (occupied) dπ orbital under the L z angular momentum operator. These two effects account for the unusual hydride chemical shift of +4.8 ppm observed experimentally for this species. Calculations reproduce hydride chemical shift data observed for [Ru( i Pr2 PCH2 CH2 P i Pr2 )2 (η 2 -O2 )H] + ( δ = −6.2 ppm) and [Ru(R2 PCH2 CH2 PR2 )2 H] + ( ca . −32 ppm, R = i Pr, Cy). For the latter, the presence of a weak agostic interaction trans to the hydride ligand is significant, as in its absence (R = Me) calculations predict a chemical shift of −41 ppm, similar to the [Ru(NHC)4 H] + analogues. Depending on the strength of the agostic interaction a variation of up to 18 ppm in hydride chemical shift is possible and this factor (that is not necessarily readily detected experimentally) can aid in the interpretation of hydride chemical shift data for nominally unsaturated hydride-containing species. The synthesis and crystallographic characterization of the BAr F 4 − salts of [Ru(IMe4 )4 (L)H] + (IMe4 = 1, 3, 4, 5-tetramethylimidazol-2-ylidene; L = P4, SO2 ; Ar F = 3, 5-(CF3 )2 C6 H3 ) and [Ru(IMe4 )4 (Cl)H] are also reported.